Improving Community Performance by Re-examining Public Services - Randall A. Cantrell (EDIS)
This is part of a series of EDIS publications that introduces readers to the concept of overall community performance and suggests minor modifications to neighborhoods, public schools, and public services that could help citizens improve their communities. This publication is for a general audience and provides a list of changes to public schools that, if enacted, may help improve a community’s performance.